Observaciones sobre el desarrollo de los frutos del ciruelo "Gigaglia" - Venero Del Carpio, Alberto (1961)
They are proved the good vegetative and commercial qualities of the “Gigaglia” plum, specially cultivated in the littoral of the Province of Buenos Aires. Said early-ripening variety was obtained, they say, from seeds by a grower of the Delta del Parana area, Argentine Republic. For its best pomol^ital study, it is observed periodically the .development of fruits in. the zone of La Plata, since the end of flotation till the moment when commercial harvest takes place. The results obtained show the existence of three diameters in fruits: vertical, major transversal and minor transversal that grow according to certain particular character and in relation with the weight increase. Finally it is established that fruits reach the commercial maturity 65 days after blooming.